2011
DOI: 10.1111/j.1439-0426.2011.01897.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sorting grids for deepwater rose shrimp (Parapenaeus longirostris) in the Eastern Mediterranean demersal trawl fishery

Abstract: The study aimed to evaluate sorting grids of 10 and 15 mm bar spacing specifically for separation of deep water rose shrimp, but including other species, in a Mediterranean multispecies demersal trawl fishery. Data were collected 15-25 October 2008 in Sıg˘acık Bay, Eastern Aegean Sea with the commercial trawler, ÔHapulog˘luÕ, using a modified bottom trawl net. A total of 22 valid hauls (12 with 10 mm, ten with 15 mm grids) were obtained. The separation rate of anglerfish was highest, with 100% for weight and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Since undersized fishes of many large-sized species, such as M. merluccius, are highly vulnerable to the minimum mesh size enforced in the Mediterranean (40 mm square or 50 mm diamond) (Brčić et al, 2018;Mytilineou et al, 2018) and a further increase of the mesh size would lose shrimps, cephalopods, and medium-sized fish, the exploitation pattern can be enhanced through: (i) increasing the trawl net selectivity by adopting grids and separators that allow the undersized fish to escape (Coll et al, 2008;Massutí et al, 2009;Aydın and Tosunoglu, 2011;Vitale et al, 2018b); (ii) delaying the size/age of the first capture of juveniles through spatial and/or temporal closures to fisheries when and where the juveniles aggregate in order to improve the fraction of fish reaching sexual maturity (Caddy, 1999(Caddy, , 2009Fiorentino et al, 2003;Garofalo et al, 2011;Colloca et al, 2015;Despoti et al, 2020;Mytilineou et al, 2020;Milisenda et al, 2021); or (iii) a combination of the two approaches.…”
Section: The Poor Exploitation Patternmentioning
confidence: 99%
“…Since undersized fishes of many large-sized species, such as M. merluccius, are highly vulnerable to the minimum mesh size enforced in the Mediterranean (40 mm square or 50 mm diamond) (Brčić et al, 2018;Mytilineou et al, 2018) and a further increase of the mesh size would lose shrimps, cephalopods, and medium-sized fish, the exploitation pattern can be enhanced through: (i) increasing the trawl net selectivity by adopting grids and separators that allow the undersized fish to escape (Coll et al, 2008;Massutí et al, 2009;Aydın and Tosunoglu, 2011;Vitale et al, 2018b); (ii) delaying the size/age of the first capture of juveniles through spatial and/or temporal closures to fisheries when and where the juveniles aggregate in order to improve the fraction of fish reaching sexual maturity (Caddy, 1999(Caddy, , 2009Fiorentino et al, 2003;Garofalo et al, 2011;Colloca et al, 2015;Despoti et al, 2020;Mytilineou et al, 2020;Milisenda et al, 2021); or (iii) a combination of the two approaches.…”
Section: The Poor Exploitation Patternmentioning
confidence: 99%
“…In particular, the studies carried out on sorting grids have revealed clear advantages associated with their use in mixed trawl fisheries, such as improved selectivity and by-catch reduction (e.g. Massutí et al 2009, Aydın andTosunoğlu 2011), a stable selection pattern during the tow (Suuronen and Sardà 2007), and a higher survival rate of specimens escaping from the grid bars compared with a conventional cod-end mesh (e.g. Brčić et.…”
Section: Introductionmentioning
confidence: 99%
“…Although all these studies point to the positive impact of sorting grids on the size at first capture of commercial fish and crustaceans (e.g. Massutí et al 2009, Aydın andTosunoğlu 2011), their adoption in Mediterranean trawl fisheries is still very low. Lack of sorting grid implementation could be linked to several causes, including fishers' resistence to changing fishing traditions and customs, and, consequently their unwillngness to modify their fishing gear substantially.…”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of this species takes place all year round, even if peak landings occur from March to July (Levi et al, 1995;Abdel Razek et al, 2006). Studies regarding the deep-water rose shrimp have primarily focused on its distribution, biology (Bombace, 1975;Lembo et al, 2000;Mori et al, 2000;Abelló et al, 2002;Bayhan et al, 2005;Arculeo, 2009), and fishery aspects (Sbrana et al, 2003;Sobrino et al, 2005;Sbrana et al, 2006;Ligas et al, 2011;Aydın and Tosuno glu, 2012). The population dynamics has been studied, in particular regarding the link between population abundance and environmental factors (Guijarro et al, 2009;Ligas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%